Implementation of Congregational Prayer at Muhammadiyah Parsorminan Elementary School, Sipirok District - Rosdiana, Rosdiana; Rosmaimuna, Rosmaimuna; Agustini, Rini; Nopriani, Jumaita (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to describe the implementation of congregational prayers at the Muhammadiyah Parsorminan Elementary School. This type of research is qualitative research with descriptive methods. The informants in this research were students, teachers and the principal of the Parsorminan Muhammadiyah school. The data collection is observation, interviews and documentation and the data checking techniques used are triangulation, extended participation and diligent observation. Meanwhile, data analysis in this research consists of data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of congregational prayers at the Parsorminan Muhammadiyah Elementary School has been going on for a long time, starting from when this madrasa was founded around 1924. The implementation of congregational prayers is mandatory for all students in grades III, IV, V and VI. Congregational noon prayers are held at the mosque near the school. Practically speaking, imams and muezzins are carried out by students as a form of education in discipline and preparation to become leaders. Next, midday prayers are held before the children come home from school, namely 1 o'clock on Monday to Thursday. The congregational noon prayer is held on time at around 12.30 and a quarter of an hour before prayer time the bell will be rung so that students come out and perform ablution for prayer. The results obtained from carrying out congregational prayers for students are: getting into the habit of praying on time, being orderly in queuing, students becoming brave and not shy and respectful and affectionate towards teachers and parents, and coming to school on time.